Single Drop Whole Blood Diagnostics: Portable Biomedical Sensor for Cardiac Troponin I Detection - Sarangadharan, Indu; Wang, Shin-Li; Sukesan, Revathi; Chen, Pei-chi; Dai, Tze-Yu; Pulikkathodi, Anil Kumar; Hsu, Chen-Pin; Chiang, Hui-Hua Kenny; Liu, Lawrence Yu-Min; Wang, Yu-Lin (Analytical chemistry (Washington), 2018)
Detection of disease biomarkers from whole blood is very important in disease prevention and management. However, new generation assays like point-of-care or mobile diagnostics face a myriad of challenges in detecting proteins from whole blood. In this research, we have designed, fabricated, and characterized a portable biomedical sensor for the detection of cardiac troponin I (cTnI) directly from whole blood, without sample pretreatments. The sensing methodology is based on an extended gate electrical double layer (EDL) gated field effect transistor (FET) biosensor that can offer very high sensitivity, a wide dynamic range, and high selectivity to target analyte. The sensing methodology is not impeded by electrostatic screening and can be applied to all types of FET sensors. A portable biomedical system is designed to carry out the diagnostic assay in a very simple and rapid manner, that allows the user to screen for target protein from a single drop of blood, in 5 min. This biomedical sensor can be used in hospitals and homes alike, for early detection of cTnI which is a clinical marker for acute myocardial infarction. This sensing methodology could potentially revolutionize the modern health care industry.